Plasmonic nanoparticles assemblies templated by helical bacteria and resulting optical activity. Issue 7 (22nd April 2020) - Feng, Wenchun; Kadiyala, Usha; Yan, Jiao; Wang, Yichun; DiRita, Victor J.; VanEpps, J. Scott; Kotov, Nicholas A.
Abstract: Plasmonic nanoparticles (NPs) adsorbing onto helical bacteria can lead to formation of NP helicoids with micron scale pitch. Associated chiroptical effects can be utilized as bioanalytical tool for bacterial detection and better understanding of the spectral behavior of helical self‐assembled structures with different scales. Here, we report that enantiomerically pure helices with micron scale of chirality can be assembled on Campylobacter jejuni, a helical bacterium known for severe stomach infections. These organisms have right‐handed helical shapes with a pitch of 1–2 microns and can serve as versatile templates for a variety of NPs. The bacteria itself shows no observable rotatory activity in the visible, red, and near‐IR ranges of electromagnetic spectrum. The bacterial dispersion acquires chiroptical activity at 500–750 nm upon plasmonic functionalization with Au NPs. Finite‐difference time‐domain simulations confirmed the attribution of the chiroptical activity to the helical assembly of gold nanoparticles. The position of the circular dichroism peaks observed for these chiral structures overlaps with those obtained before for Au NPs and their constructs with molecular and nanoscale chirality. This work provides an experimental and computational pathway to utilize chiroplasmonic particles assembled on bacteria for bioanalytical purposes. Abstract : Gold nanoparticles assemble onto the surface of helical bacterium, Campylobacter jejuni, producing right‐handed helices with a pitch of 1–2 microns. The bacterial dispersion acquires chiroptical activity at 500–750 nm that matches the calculated chiroplasmonic spectra. This study provides a pathway to utilize chiroplasmonic particles for monitoring shape dynamics of bacteria and identification of helical bacteria in complex microbiomes.